2003
DOI: 10.1046/j.1365-2141.2003.04284.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult bone marrow is a rich source of human mesenchymal ‘stem’ cells but umbilical cord and mobilized adult blood are not

Abstract: Summary. In postnatal life, mesenchymal stem cells (MSC) self-replicate, proliferate and differentiate into mesenchymal tissues, including bone, fat, tendon, muscle and bone marrow (BM) stroma. Possible clinical applications for MSC in stem cell transplantation have been proposed. We have evaluated the frequency, phenotype and differentiation potential of MSC in adult BM, cord blood (CB) and peripheral blood stem cell collections (PBSC). During culture, BM MSC proliferated to confluence in 10-14 d, maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
365
3
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 583 publications
(411 citation statements)
references
References 28 publications
18
365
3
18
Order By: Relevance
“…2 Cells from HDC patients display a mixed morphology in primary culture. Representative phase-contrast images of primary cultures derived from a patients who have received no prior treatment and b patients who had received prior highdose chemotherapy long-term culture conditions developed the same microscopic appearance as stroma derived from fresh marrow buffy coat samples as reported by Wexler et al [23]. All cultures were primarily seeded with hematopoietic CD34 + cells derived from the same cord blood source.…”
Section: Hematopoietic Colony-forming Assaymentioning
confidence: 58%
See 1 more Smart Citation
“…2 Cells from HDC patients display a mixed morphology in primary culture. Representative phase-contrast images of primary cultures derived from a patients who have received no prior treatment and b patients who had received prior highdose chemotherapy long-term culture conditions developed the same microscopic appearance as stroma derived from fresh marrow buffy coat samples as reported by Wexler et al [23]. All cultures were primarily seeded with hematopoietic CD34 + cells derived from the same cord blood source.…”
Section: Hematopoietic Colony-forming Assaymentioning
confidence: 58%
“…To ensure that a homogenous population of MSCs had been cultured, immunophenotyping of surface markers, using flow cytometric techniques, was carried out according to previous reports [1,23,24]. MSCs were examined using the fluorescently tagged monoclonal antibodies anti-CD105, anti-CD45, anti-CD166, anti-CD44, and anti-CD29 (BD Biosciences, Oxford, UK).…”
Section: Immunophenotyping Msc Culturesmentioning
confidence: 99%
“…The frequency of MSC in cryopreserved UCB units has not been clearly defined. Previous studies reported that the frequency of BM-MSC in adults was one in 3.4 Â 10 4 cells, using the culture of colony forming unit-fibroblast (CFU-F) as a surrogate assay, while fresh UCB and PBSC did not produce CFU-F at all [13,21]. It is possible that MSCs in cryopreserved UCB units are present at a very low frequency relative to MSCs in BM in our samples.…”
Section: Discussionmentioning
confidence: 82%
“…It was reported that fresh UCB-derived mononuclear cells (MNCs) seeded on flasks without supportive stromal layers did not form stroma in long-term culture conditions [12]. Wexler et al [13] concluded that neither fresh UCB nor peripheral blood with stem cell mobilization contained MSCs. Another study also reported that fresh UCB did not produce mesenchymal progenitor cells [14].…”
mentioning
confidence: 99%
“…A standard colony-forming-unit fibroblastic (CFU-F) assay was used to calculate MSC frequency within the BMMC fraction [29,30]. Briefly, day-0 BMMCs were seeded at 5 different concentrations (10 · 10 3 -200 · 10 3 cells) in 60 mm culture dishes (Gibco) and expanded for 14 days.…”
Section: Msc Quantification In the Bm Mononuclear Cell Fractionmentioning
confidence: 99%